2022
DOI: 10.1021/acssuschemeng.1c07148
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Nanocellulose/Carbon Nanotube Composite Aerogels for High-Efficiency Electromagnetic Interference Shielding

Abstract: Bio-based specialized components have emerged as a promising trend to limit the use of petroleum derivatives. Conversely, the current use of electronic systems has conditioned the emission of electromagnetic waves that interfere with high-precision devices and harm human health. Thus, robust, ultralight, and conductive nanocellulose-based aerogels paired with carbon nanotubes appear as an electromagnetic interference (EMI) shielding biomaterial to reduce the dispersion of microwaves emitted or received from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 71 publications
1
27
0
Order By: Relevance
“…This might be attributed to destruction of molecular structure during the reclaiming process. The effective formation of segregated CNT structure and the low percolation threshold in HX-RR can be an advantage for flexible strain sensor ,, and EMI shielding applications. , The utilization of recycled rubber to fabricate conductive rubber not only reduces the production cost but also promotes a circular economy model.…”
Section: Results and Discussionmentioning
confidence: 99%
“…This might be attributed to destruction of molecular structure during the reclaiming process. The effective formation of segregated CNT structure and the low percolation threshold in HX-RR can be an advantage for flexible strain sensor ,, and EMI shielding applications. , The utilization of recycled rubber to fabricate conductive rubber not only reduces the production cost but also promotes a circular economy model.…”
Section: Results and Discussionmentioning
confidence: 99%
“…All of the experimental materials except cotton were purchased from Aladdin Chemical Reagent Company (China) and used without further purification. The cotton was composed of 80% cotton and 20% polyester, and was bought from Wanchang Weaving Co., Ltd. (Jinzhou, China); the gram weight was 105 g/m 2 .…”
Section: ■ Experimental Detailsmentioning
confidence: 99%
“…Both of the two techniques could enable more EM waves to enter the shielding materials instead of reflection with increasing EM absorption. [1][2][3]6,22 Up to the present, although research on and companies manufacturing the lower-reflection shielding (SE R ) materials have made considerable progress, the major shortcoming is the tension between performance and density. 6−9,12−16 In this study, a textured porous conductive material was fabricated by electroless nickel plating (ECP-Ni) and carbonization technology and used as EM shielding material (An cotton).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Increase EMI shielding effectiveness for application in which beside thermal insulation, shielding is also required , the cover also needs to provide shield against penetration for electromagnetic waves. Study in ref 214 , suggested an effective aerogel method to block radiation by combining sodium alginate, cationic CNCs, and TEMPO-oxidized cellulose nanofibrils with carbon nanotubes at different concentrations.…”
Section: Aerogelsmentioning
confidence: 99%